Desenvolvimento de curativo a base de quitosana e gelatina contendo óleo de copaíba para tratamento de queimados - Genesi, Bianca Pereira [UNIFESP] (2015)
The importance of skin lesions has suggested studies for obtaining biomaterials in order to reduce healing time, enhance the healing quality and promote patient comfort, especially for the relief of pain. Healing, anti-inflammatory and antibiotic properties can be enhanced by the addition of herbal medicines, like copaiba oil (Copaifera sp.), to the films used as wound dressings. Biopolymers films from chitosan and gelatin have attracted much attention because they are nontoxic, hemostatic, biocompatible, antimicrobial, and they supposedly accelerate the healing process. Emulsified films with several chitosan/gelatin ratios, with or without copaiba oil, were prepared by the simultaneous homogenization of chitosan and gelatin solutions followed by the casting and slow drying on a flat support (Casting technique). Films were characterized by physical-chemical analysis like color parameter, barrier properties, mechanical properties, scanning electron microscopy, infrared spectroscopy, and thermal analysis, besides the biological analysis to ensure the biosafety of dressing like microbial permeation, antimicrobial activity, cytotoxicity and cell adhesion. The results indicated that the film containing the same proportions of the biopolymers (50%:50%) with copaiba oil (0.5%) presented the best physical and in vitro biological properties and that it has the potential to be evaluated in vivo. Concerning the physicochemical properties, it was observed that the films showed barrier and mechanical properties suitable for use as wound dressings. The micrographs obtained by scanning electron microscopy showed that the copaiba oil presented good dispersion in the biopolymers matrix. The thermal analysis, infrared and mechanical properties suggested the formation of a biopolymeric polyelectrolyte complex. The antimicrobial activity of the films was observed in relation to the assessed microorganisms. The results demonstrated the potential anti-microbial properties of the films and it was observed that the test on solid medium was the most effective compared to the assay in a liquid medium, due to interference that occurred when the films were in contact with the culture medium, resulting in higher absorption values. Cytotoxic properties of these films were evaluated showing that they are safe and nontoxic. Cell adhesion tests showed that the cells do not adhere to the film, which is a desirable characteristic for wound dressings.